Silverlight Recipes A Problem-Solution Approach - Ghosh, Jit.; Cameron, Rob.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Silverlight Recipes: A Problem-Solution Approach, Second Edition is your practical companion to developing rich, interactive web applications with Microsoft$1 (Bs latest technology. This book tackles common problems and scenarios that on-the-job developers face every day by revealing code and detailed solutions. You$1 (Bll quickly be able to integrate real-world, functioning code into your applications$1 (Band save hours of coding time. The recipes included in Silverlight Recipes have been carefully selected and tested with the professional developer in mind. You$1 (Bll find problems stated clearly and succinctly, artful solutions explored, and ample discussion of the code and context so you're immediately clear how the solution will support your project. You'll also discover the innovations presented in Silverlight 4 and how to effectively employ them. Enjoy practical coverage of Silverlight development in many projects and contexts, including: Designing complete, rich, interactive user experiences Manipulating content and the runtime environment through the Silverlight Plug-in Runtime API Consuming, transforming, and displaying content in your Silverlight web application through XML, LINQ-based data access, and isolated storage Building custom controls for your Silverlight project Integrating rich media, including audio and video, to create a very dynamic user interface and experience Using new Silverlight features, including .NET Framework integration, the use of dynamic languages like Python and Ruby in Silverlight development, and digital rights management support Find instant solutions, comprehensive Silverlight coverage, and time-saving expert advice, all in one book.s
A Quick Tour of Silverlight 4 Development -- Application Design and Programming Model -- Developing User Experiences -- Data Binding -- Controls -- Browser Integration -- Networking and Web Service Integration -- Building Out Of Browser Silverlight Applications -- Building LOB Applications -- Integrating Rich Media -- Integrating Microsoft IIS Smooth Streaming.
Keywords: Computer science; Computer Science; Programming Languages, Compilers, Interpreters